Are paternal or grandmaternal age associated with higher probability of trisomy 21 in offspring? A population‐based, matched case‐control study, 1995‐2015. Issue 3 (1st December 2020) - Schliep, Karen C.; Feldkamp, Marcia L.; Hanson, Heidi A.; Hollingshaus, Michael; Fraser, Alison; Smith, Ken R.; Panushka, Katherine A.; Varner, Michael W.
Abstract: Background: Fetal aneuploidy risk increases with maternal age, but the majority of pregnancies complicated by trisomy 21 occur in younger women. It has been suggested that grandmaternal and/or paternal age may also play a role. Objectives: To assess the association between grandmaternal and paternal age and trisomy 21. Methods: For the grandmaternal assessments, we included all offspring with trisomy 21 in a statewide birth defects surveillance system (1995‐2015) that could be linked to 3‐generation matrilineal pedigrees in the Utah Population Database. Ten sex/birth year‐matched controls were selected for each case (770 cases and 7700 controls). For the paternal assessments, our cohort included all trisomy 21 cases (1995‐2015) where both the mother and father resided in Utah at the time of birth (1409 cases and 14 090 controls). Ages were categorised by 5‐year intervals (reference: 25‐29 years). Conditional logistic regression, adjusting for potential confounding factors, was used to model the association between grandmaternal and paternal age and trisomy 21. Results: No association between grandmaternal age and trisomy 21 was detected, whether age was assessed continuously (adjusted odds ratio [OR] 1.01, 95% confidence interval [CI] 0.98, 1.03) or categorically after adjusting for grandmaternal and grandpaternal race/ethnicity and grandpaternal age. Compared to fathers aged 20‐29 years, fathers <20 years (OR 3.15, 95% CI 1.99, 4.98) and 20‐24 years (OR 1.39, 95% CI 1.11, 1.73) had increased odds of trisomy 21 offspring, after adjusting for maternal and paternal race/ethnicity and maternal age. Results were consistent after excluding stillbirths, multiples, and trisomy 21 due to translocation or mosaicism. Conclusions: Maternal age is an important risk factor for trisomy 21 offspring; however, this population‐based study shows that that young paternal age is also associated with trisomy 21, after taking into account maternal age and race/ethnicity.